PEMANFAATAN EDUWISATA GRIHA LITERA TERHADAP MINAT LITERASI LINGKUNGAN SISWA DI SDN BANJAR KERTEK - Fedrico Amarki; Ahmad Khoiri; Desty Putri Hanifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the utilization of Griha Litera educational tourism in fostering students’ environmental literacy interest at SDN Banjar Kertek. Environmental literacy is an important competency for elementary school students as it relates to their understanding, attitudes, and behaviors in caring for the environment. However, in reality, environmental literacy among elementary students is still relatively low, as indicated by low awareness of environmental cleanliness, weak reading habits related to environmental issues, and limited student participation in environmental preservation activities. This research employed a descriptive quantitative method with the population consisting of fourth-grade students at SDN Banjar Kertek. The sampling technique used was saturated sampling. Data were collected through questionnaires, observations, documentation, and structured interviews. Data analysis was conducted using descriptive statistics including mean, median, mode, standard deviation, and qualitative analysis. The results showed that the utilization of Griha Litera educational tourism was categorized as good and contributed positively to students’ environmental literacy interest. Students demonstrated interest in environmental-themed reading materials, active involvement in field activities, and caring attitudes toward the surrounding environment. It is recommended that schools integrate educational tourism and experiential learning activities continuously as a strategy to improve students’ environmental literacy from an early age.